P-TEFb Regulates Transcriptional Activation in Non-coding RNA Genes - Bunch, Heeyoun; Choe, Hyeseung; Kim, Jongbum; Jo, Doo Sin; Jeon, Soyeon; Lee, Sanghwa; Cho, Dong-Hyung; Kang, Keunsoo (Frontiers in Genetics, 2019)
Many noncoding RNAs (ncRNAs) serve as regulatory molecules in various physiological pathways including gene expression in mammalian cells. Distinct from protein-coding RNA expression, ncRNA expression is regulated solely by transcription and RNA processing/stability. Transcriptional regulation in ncRNA genes is thus important to be understood and is yet to be known completely. Previously, we identified that a subset of mammalian ncRNA genes is transcriptionally regulated by RNA polymerase II (Pol II) promoter-proximal pausing and in a tissue-specific manner. In this study, human ncRNA genes that are expressed in the early G1 phase, termed immediate early ncRNA genes, were monitored to assess the function of positive transcription elongation factor b (P-TEFb), a master Pol II pausing regulator for protein-coding genes, in ncRNA transcription. Our findings indicate that the expression of many ncRNA genes is induced in the G0–G1 transition and regulated by P-TEFb. Interestingly, a biphasic characteristic of P-TEFb-dependent transcription of serum responsive ncRNA genes was observed: Pol II carboxyl-terminal domain phosphorylated at serine 2 (S2) was largely increased in the transcription start site (TSS, –300 to +300) whereas overall, it was decreased in the gene body (GB, > +350) upon chemical inhibition of P-TEFb. In addition, the three representative, immediate early ncRNAs, whose expression is dependent on P-TEFb, metastasis associated lung adenocarcinoma transcript 1 (MALAT1), nuclear enriched abundant transcript 1 (NEAT1), and X-inactive specific transcript (XIST), were further analyzed for determining P-TEFb association. Taken together, our data suggest that transcriptional activation of many human ncRNAs utilizes pausing and releasing Pol II and that the regulatory mechanism of transcriptional elongation in these genes requires the function of P-TEFb. Furthermore, we propose that ncRNA and mRNA transcription are regulated by similar mechanisms while P-TEFb inhibition unexpectedly increases S2 Pol II phosphorylation in the TSSs in many ncRNA genes.